Importance of the Northward IMF for the Quasistatic Mesoscale Field‐Aligned Currents Embedded in the Diminished Region 1/2 Current System in the Dusk Sector. Issue 8 (27th July 2021) - Yokoyama, Y.; Taguchi, S.; Iyemori, T.
Abstract: To understand the features of the quasistatic field‐aligned currents (FACs) consisting of multiple mesoscale (∼10–100 km) upward and downward FAC regions in the duskside auroral oval, we examined the magnetic field data obtained through the constellation measurements of Swarm satellites for a duration of more than three years. We introduced a method of automated event identification and took the events in 577 satellite orbits that pass through the high‐latitude part of the 14–18 magnetic local time auroral oval. The results of the analysis reveal that the occurrence ratio of the FAC events increases with the IMF B Z, and that the event can be detected at a ratio exceeding 20% for B Z greater than 1 nT. This indicates that the quasistatic mesoscale FACs in the duskside sector are pertinent to a northward IMF condition and that they are not a simple remnant of the diminished Region 1. The results also show that the FAC density tends to increase with the solar wind proton density, implying that the latter is directly associated with FAC generation. The FAC events can occur in a wide range of solar zenith angles, that is, 65–135°, indicating that whether the ionosphere is sunlit or dark is not crucial for the appearance of the event. These results strongly suggest that multiple mesoscale FACs are produced in the low‐latitude boundary layer through a mechanism related to solar wind plasma entry processes that can be more easily attained as the northward component of the IMF increases. Key Points: As the IMF B Z increases, mesoscale multiple quasistatic field‐aligned currents embedded in the diminished dusk Region 1/2 become prominent The density of the mesoscale field‐aligned currents tends to increase with the solar wind proton density The event appears regardless of whether the ionosphere is sunlit or dark